Identification of bluetongue virus VP6 protein as a nucleic acid-binding protein and the localization of VP6 in virus-infected vertebrate cells. - Roy, P (1990)
Recently the insect baculovirus Autographa californica nuclear polyhedrosis virus (AcNPV) has been effectively adapted as a highly efficient vector in insect cells for the expression of various genes. A cDNA sequence of RNA segment 9 of bluetongue virus serotype 10 (BTV-10, an orbivirus member of the Reoviridae family) encoding a minor core protein (VP6) has been inserted into the BamHI site of the pAcYM1 transfer vector derived from AcNPV. Spodoptera frugiperda cells were cotransfected with the derived vector in the presence of authentic AcNPV DNA to produce recombinant viruses. These synthesized significant amounts of a protein (representing ca. 50% of the stained cellular protein) similar in size and antigenicity to the authentic BTV VP6. The expressed protein was identified as a nucleic acid-binding protein by using an RNA overlay-protein blot assay. A polyclonal anti-VP6 serum prepared by using the expressed VP6 protein has been used in an immunogold procedure to locate VP6 in BTV-infected mammalian cells. Gold was found to be associated with the matrix of virus inclusion bodies (VIB), with viruslike particles in the VIB, as well as with mature virion particles that were in close proximity to the VIB or were released from cells and adsorbed to cell surfaces. The recombinant virus antigen has also been used to identify antibodies to different BTV serotypes in infected sheep sera, indicating the potential of the expressed protein as a group-reactive antigen for the diagnosis of BTV infections.